Supporting Students Become A Smart User Through TEDTalk Application - Chusnul Chotimah; Fitri Handayani (Lingua, 2020)
Abstract This research is aboutTed Talk application that support the students being smart people by smartphone. TED Talk applications can help the students in learning English for four skills such as reading writing listening and speaking. This app offers kids and parents the opportunity to explore and view videos from the renowned TED (Technology, Entertainment, Design) conferences, which feature a mix of interesting speakers from all walks of life. The researcher believes that this application can support the students being smart people by smartphone. The purpose of this research is to support the students being smart people by their smartphone using TED Talk application. This research did about six months in As-Syafi’iyah Islamic University. The participants in this research are 20 college students on fifth semester in speaking for academic purposes subject. The method of this research is descriptive qualitative. The instruments that used in this research are interview and observation. And based the data, the researcher can conclude that using TED Talk as application that support the students being smart people by smartphone is very useful for all students. The students can increase their knowledge and skills in English. They can watch videos or listening audio to get some ideas for speaking practice.